Menentukan Kerangka Kerja Manajemen Proyek Perusahaan - Rahayu Ary Yuniarti; Hendra S. T. (ComTech: Computer, Mathematics and Engineering Applications, 2011)
Every business has a vision for its business plan. Sometimes they face a problem on how to deliver a business plan into a detailed project to achieve their vision. Developing an enterprise project management is one of effective business principles and systems for guiding and organizing that functions to deliver a business plan and to align and integrate processes and information systems. Enterprise project management is a systematic approach for program management and is based on the principle that the vision, mission, and objectives of organization are a set of projects. When effectively defined, planned, integrated, and communicated, business is provided with a totally different view of your organization's ability to define and achieve its objectives. Moving an organization from an old fashioned project management view to the Enterprise Project Management is a shift that is both technical and cultural.